'Stigma: the cul-de-sac of the double bind' the perspective of Turkiye; a phenomenological study - BAYRI BİNGÖL, FADİME (WILEY, 2014)
The aim of this study was to explore and describe the stigmatization experienced by individuals with mental health problems (IMHP) and the relationships between stigmas associated with mental health problems, psychiatric diagnoses, treatments, and social environments and their consequences. Thirty-three IMHP were recruited from outpatient and day clinics at the psychiatry department of a university hospital within a 5-month time period for this qualitative, descriptive study. Data were gathered using a structured interview form with open-ended questions to explore the changes in everyday life experienced by IMHP during the course of their illness. Data were analysed using the Colaizzi method of analysis. Our findings show that almost all IMHP were concerned about being stigmatized by others, society, their family, and health care professionals. Another concern that IMHP reported was self-stigmatization. Stigmatization serves as a barrier to treatment adherence and socialization in IMHP. Furthermore, stigmatization has a significant impact on the lives of IMHP, and methods of coping with stigmatization are commonly ineffective. However, stigmatization can be reduced by dealing with the illness, IMHP, their relatives, and professionals in an unprejudiced manner.
Keywords: culture; ethinicity; mental health; nursing; qualitative methodology; stigma; MENTAL-ILLNESS; SELF-STIGMA; PEOPLE; STIGMATIZATION; DISORDERS; HEALTH; CARE; EXPERIENCES; RELATIVES; HELP